KEBEBASAN BERAGAMA DAN PROBLEMATIKA HAM UNIVERSAL - Akhmad Muamar (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2013)
Today, human rights are always referenced as a measure of freedom to behave. This model of human rights is a typical Western worldview and forced to be applied in all areas, including in converting to other religions. Indeed, human rights and freedom of religion are containing the freedom to follow or embrace any religion or belief which believed. Everyone has the freedom, either individually or community, in public or private space, to manifest his religion or belief in teaching and worshiping. These rights andfreedoms are not absolute. If someone demands his rights, he is required to fulfill the obligations of human. Moreover, human rights are essentially limited by the rights of others. The existence of the universal Declaration of Human Rights brings a new problem, because of one of its clause guarantees and protects a person’s right to change his religion or faith. This is certainly contrary to Islam which forbids its ummah to change their religion. Because of this problem, the paper discusses the problems related to universal human rights and religious freedom.